Assessment of selected physics teachers' readiness to use constructivism as a teaching approach and its effects on their classroom practices - Aumento, Aileen Songalia (Animo Repository, 1998)
This study was aimed at assessing the readiness of selected physics teachers to use constructivism as a teaching approach and determining the changes it produced on their classroom practices. In SY 1997-1998, four secondary school physics teachers from Metro Manila were chosen as participants (Ss). After a brief, but thorough training on constructivism, the Ss were made to use a teaching unit on Energy later, the difficulties they encountered, the changes they have to make to accommodate the approach, and the benefits they gained were investigated qualitatively through the use of journals, observation checklists, interviews, fieldnotes, and videotapes of a teaching session. A validated survey questionnaire called Constructivist Learning Environment Survey (CLES) was administered to the students of the Ss to establish the students' perceptions of the teaching-learning environment. The study revealed that the Ss encountered several difficulties in changing to a constructivist approach: (1) the possibility of not finishing the syllabus during the time table set, (2) the unsuitability of the constructivist approach to their less intelligent students, (3) the inability of the students to express themselves in English, the language used to teach physics, (4) the intensity of preparation that the teachers had to do, (5) the manner of evaluating the students, (6) the fear of loss of classroom control, and (7) the large class size and lack of materials. On the other hand, the Ss perceived the need to act as a facilitator, not as a controller inside the classroom, (4) initiating experiments and simple activities, (5) the need for more intensive preparation, (6) the need for more students' consultation, and (7) the need to initiate and encourage student-led discussions. Also, the Ss realized these benefits from the use of constructivism (1) more self-confidence on the part of the students, (2) broadened knowledge on the part of the teacher, (3) more harmonious relationship between the teacher and students, (4) more intellectual stimulation for the teacher, and (5) the ability to address more issues inside the classroom. The observation checklist revealed that the participants displayed more constructivist teaching practices, specifically those geared towards giving the students more responsibility for their learning, after the use of the teaching unit. In sum, the Ss found constructivism a beneficial alternative to their regular teaching approach provided they undergo necessary changes and were properly trained. Further studies could be done on the suitability of constructivism to the Philippine educational system in relation to student achievement, and the possibility of incorporating it into the teachers' preservice education.